Is cultured meat a promising consumer alternative? Exploring key factors determining consumer's willingness to try, buy and pay a premium for cultured meat. (1st December 2022) - Rombach, Meike; Dean, David; Vriesekoop, Frank; de Koning, Wim; Aguiar, Luis Kluwe; Anderson, Martin; Mongondry, Philippe; Oppong-Gyamfi, Mark; Urbano, Beatriz; Gómez Luciano, Cristino Alberto; Hao, Wendy; Eastwick, Emma; et al.
Abstract: Cultured meat is a relatively new product, enjoying consumer appreciation as a more sustainable meat option. The present study builds on a sample from a diverse set of countries and continents, including China, the US, the UK, France, Spain, Netherlands, New Zealand, Brazil, and the Dominican Republic and uses partial least square structural equation modelling. The proposed conceptual model identified key factors driving and inhibiting consumer willingness to try, buy, and pay a price premium for cultured meat. Results relate to the overall sample of 3091 respondents and two sub-sample comparisons based on gender and meat consumption behaviour. Food neophobia, having food allergies, being a locavore, and having concerns about food technology were found to be inhibiting factors towards willingness to try, buy, and pay a price premium for cultured meat. Food curiosity, meat importance, and a consumer's perception of cultured meat as a realistic alternative to regular meat were found to be important drivers that positively impacted consumers' willingness to try, buy and pay more. Best practice recommendations address issues facing marketing managers in food retail and gastronomy.